(Pro)renin receptor antagonist PRO20 attenuates nephrectomy‐induced nephropathy in rats via inhibition of intrarenal RAS and Wnt/β‐catenin signaling. Issue 11 (31st May 2021) - Wang, Yan; Wang, Yurong; Xue, Kai; Wang, Huaijie; Zhou, Jingjing; Gao, Feng; Li, Chengde; Yang, Tianxin; Fang, Hui
Abstract: Introduction: (Pro)renin receptor has emerged as a new member of the renin‐angiotensin system implicated in the pathogenesis of chronic kidney disease (CKD). Herein we report characterization of the therapeutic potential of (pro)renin receptor (PRR) antagonist PRO20 in 5/6 nephrectomy (5/6Nx) rats. Methods: Male Wistar rats underwent 5/6Nx followed by treatment with vehicle or received daily injections of a PRR inhibitor PRO20 (700 μg/kg) via the 3 s.c. Sham group served as a control. Results: As compared with the sham control, the 5/6Nx rats exhibited significant increases in proteinuria, glomerulosclerosis, tubular injury, and interstitial inflammation in the remnant kidneys. Treatment with PRO20 significantly attenuated these abnormalities, as evidenced by reduced expression of fibronectin, α‐SMA, collagen 1, TGF‐β1, IL‐6, IL‐8, IL‐1β, MCP‐1 and increased expression of E‐cadherin. Increased urinary/renal levels of renin activity, angiotensinogen (AGT), and Angiotensin II (Ang II) by 5/6Nx, which were all ameliorated by PRO20. Renal PRR, the secreted proteolytic fragment of PRR (sPRR) in renal and urinary, were all elevated in 5/6Nx rats. Moreover, our results revealed that renal Wnt3A and β‐catenin expression were upregulated during 5/6Nx, which were all attenuated by PRO20. Conclusions: Overall we conclude that in vivo antagonism of PRR with PRO20 will improve 5/6Nx‐induced CKD mainly through inhibition of intrarenal RAS and Wnt/β‐catenin signaling pathway.